Effect of the COVID‐19 pandemic on anxiety among children with cystic fibrosis and their mothers - Pınar Senkalfa, Burcu (Pediatr Pulmonol, 2020)
BACKGROUND: We aimed to evaluate anxiety among children with cystic fibrosis (CF) and their mothers related to the COVID‐19 pandemic. METHODS: A total of 45 patients with CF and their mothers were enrolled in the study together with 90 age‐matched healthy children and their mothers as a control group. The State and Trait Anxiety Inventory (STAI) was administered by teleconference with children aged 13 to 18 years old and their mothers. The STAI for children was administered with children aged 9 to 12 years. Results were compared with age‐matched healthy children and their mothers. The relationship between anxiety scores of children with CF and their mothers was evaluated by comparing with clinical data of children with CF. At the conclusion of the teleconference, mothers were asked whether their anxiety had changed as a result of the interview. RESULTS: It was found that healthy children aged 13 to 18 years had higher state anxiety scores than age‐matched children with CF. Mothers of children with CF had higher trait anxiety scores, especially those of children aged 0 to 12 years, than mothers of healthy children (P < .05). For mothers of children with CF, state anxiety scores were higher among those whose children had chronic Pseudomonas infection (P < .05). Most mothers of children with CF stated that their anxiety decreased following the interview. CONCLUSION: The COVID‐19 pandemic may increase anxiety among mothers of children with CF as well those with healthy children. However, COVID‐19 had no effect on the anxiety of children with CF. Informing parents of children with CF about COVID‐19 by teleconference may decrease anxiety.